2016
DOI: 10.1103/physreva.94.043407
|View full text |Cite
|
Sign up to set email alerts
|

Double-electron recombination in high-order-harmonic generation driven by spatially inhomogeneous fields

Abstract: We present theoretical studies of high-order harmonic generation (HHG) driven by plasmonic fields in two-electron atomic systems. Comparing the two-active electron and single-active electron approximation models of the negative hydrogen ion atom, we provide strong evidence that a double non-sequential two-electron recombination appears to be the main responsible for the HHG cutoff extension. Our analysis is carried out by means of a reduced one-dimensional numerical integration of the two-electron time-depende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…At this very low inhomogeneity degree of β = 0.005 a.u., and low IR peak intensity, this enhancement of the 2e-ionization rate is a very surprising result. Similar behaviour was previously observed in [15], where the double-electron ionization reaches higher yields leading to an enhancement in the intensity of the HHG signal. However, in that latter case a larger inhomogeneity degree of β = 0.02 a.u was used.…”
Section: He + and He 2+ Ion Yieldssupporting
confidence: 87%
See 1 more Smart Citation
“…At this very low inhomogeneity degree of β = 0.005 a.u., and low IR peak intensity, this enhancement of the 2e-ionization rate is a very surprising result. Similar behaviour was previously observed in [15], where the double-electron ionization reaches higher yields leading to an enhancement in the intensity of the HHG signal. However, in that latter case a larger inhomogeneity degree of β = 0.02 a.u was used.…”
Section: He + and He 2+ Ion Yieldssupporting
confidence: 87%
“…[14] for more details). However, since recent studies of post-ionization dynamics in spatially inhomogeneous fields [15] provides new physical effects and insights, a question arises as to the influence of spatial variation on the DI process. The aim of this work is to present a complete study of DI driven by plasmonic-enhanced spatially inhomogeneous fields with an investigation of NSDI in general, and the RESI and RIDI mechanisms in particular.…”
Section: Introductionmentioning
confidence: 99%
“…To this end we employ the numerical solutions of the reduced 1D×1D-TDSE for both the two-active electron (TAE) and the single active electron (SAE) models. From these models, we plan to trace out the analogies and differences in the HHG process from these two atomic systems, a priori very similar in their intrinsic structure (Chacón et al, 2015b).…”
Section: Other Processesmentioning
confidence: 99%
“…For instance, the behaviour of complex systems, e.g. multielectronic atoms and molecules, under the influence of spatial inhomogeneous fields is an unexplored area -only few attempts to tackle this problem has been recently reported (Chacón et al, 2015b;Yavuz et al, 2016Yavuz et al, , 2015. In addition, and just to name another example, it was recently demonstrated that Rydberg atoms could be a plausible alternative as a driven media (Tikman et al, 2016).…”
Section: Conclusion Outlook and Perspectivesmentioning
confidence: 99%
“…For instance, the behaviour of complex systems, e.g. multielectronic atoms and molecules, under the influence of spatial inhomogeneous fields is an unexplored area -only few attempts to tackle this problem has been recently reported [97,137,138]. In addition, and just to name another example, it was recently demonstrated that Rydberg atoms could be a plausible alternative as a driven media [139].…”
Section: Conclusion Outlook and Perspectivesmentioning
confidence: 99%